Intensity modulated radiation therapy technique in the treatment of gynecologic malignancies - Sirák, I; Kasaová, L; Petera, J; Vosmik, M; Zoul, Z (Ceská gynekologie, 2010)
A description of intensity modulated radiation therapy (IMRT) technique and its implementation in the treatment of gynecologic malignancies. A review article. Department of Oncology and Radiotherapy, University Hospital in Hradec Králové. General explanation of IMRT priciples, its benefits and limitations, and a review of published data about its utilization in the treatment of endometrial, cervical, and vulvar carcinoma. IMRT represents an accessible and highly conformal external beam radiothrapy technique, which enables a significant sparing of healthy tissue with consequent reduction of radiation morbidity in comparison with other conventional and conformal techniques. A feasibilty of dose excalation with preservation of low toxicity is another advandage of IMRT. It can be utilized in the treatment of most frequent gynecologic tumors, especially in endometrial, cervical, and vulvar carcinoma.